The Evolution of Philosophical Interpretation in Islam: From Classical to Modern - Haikal, Reyazul Jinan; Firdaus, Zhilal Fajar (UIN Sunan Gunung Djati Bandung, 2024)
This research examines the evolution of philosophical interpretation (tafsir falsafi) from the classical to the modern period within the context of the Islamic intellectual heritage. Philosophical interpretation, integral to the journey of Muslim scholars since the classical era, serves as a